Zui bang de ji mi - Buitrago, Jairo (Qi cai yun tu shu guan, 2018)
El brazo de Jimmy es largo y fuerte. Y sus pies rápidos. Ya dicen en el pueblo cuando lo ven entrenar que, "flota como mariposa, pica como abeja.". - Inspired by Muhammad Ali, Jimmy starts training to become a boxer, and while his future looks bright, he decides leaving his small town for big matches might not be the best option for him